Exploring the Implementation of “Merdeka Belajar Kampus Merdeka” in Indonesian Islamic Universities - Mahmud, Muchammad Eka; Setyoningrum, Muthia Umi; Kholifah, Yusnia Binti (JURNAL AL-TANZIM, 2024)
“Merdeka Belajar Kampus Merdeka” (MBKM) is an Indonesian government program launched to improve students’ skills and competencies, both hard and soft skills. This study aims to analyze the implementation strategy of the “Merdeka Belajar Kampus Merdeka” (MBKM) program in Islamic Religious Colleges (PTKI) in Indonesia. Using a qualitative approach and a multi-case study method, this study examines the implementation of MBKM in Islamic religious colleges in Indonesia. Data were collected through in-depth interviews, observation and documentation. Data were analyzed using multi-case analysis techniques, starting from single case analysis/individual case and continuing with cross-case analysis/cross-case analysis. After being analyzed, data validity was checked through the degree of certainty, transferability, and trustworthiness. The results of this study indicate that implementing MBKM in PTKI uses a curriculum overhaul and adaptation strategy. The curriculum overhaul is implemented through learning innovation programs, collaboration, learning opportunities, eight program learning opportunities, character education, and curriculum models. Implementing curriculum adaptation is carried out through the ease of opening new study programs, study program accreditation, and the right to study outside the program for three semesters. The MBKM program is evaluated internally through internal quality audits and externally through national and international accreditation.